2013
DOI: 10.3897/biorisk.8.3251
|View full text |Cite
|
Sign up to set email alerts
|

Amphibians as indicators of changes in aquatic and terrestrial ecosystems following GM crop cultivation: a monitoring guideline

Abstract: Amphibians are a suitable indicator group for monitoring possible negative direct or indirect effects of GMO cultivation at the individual and population level. Direct effects could occur in aquatic ecosystems via uptake of GM pollen or GM detritus by anuran larvae. However, indirect negative effects caused by changes in cultivation practices (changes in pesticide use, for instance) are more likely. The VDI Guideline 4333 aims to ensure comprehensive monitoring of the different life-stages of anuran species th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…For example, pesticide residues can be found in many European surface waters above environmental quality standards (Malaj et al 2014) and the National Action Plan on Sustainable Use of Plant Protection Products of the German Federal Ministry of Food, Agriculture and Consumer Protection states the same, especially for small water bodies, which are situated in the agrarian landscape (Federal Ministry of Food, Agriculture and Consumer Protection 2013). In such small ponds, pollutants can accumulate, and they are critical breeding habitat for most amphibian species (Mann et al 2003;Böll et al 2013). Worldwide, amphibian populations are decreasing at alarming rates (Houlahan et al 2000;Stuart et al 2008).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, pesticide residues can be found in many European surface waters above environmental quality standards (Malaj et al 2014) and the National Action Plan on Sustainable Use of Plant Protection Products of the German Federal Ministry of Food, Agriculture and Consumer Protection states the same, especially for small water bodies, which are situated in the agrarian landscape (Federal Ministry of Food, Agriculture and Consumer Protection 2013). In such small ponds, pollutants can accumulate, and they are critical breeding habitat for most amphibian species (Mann et al 2003;Böll et al 2013). Worldwide, amphibian populations are decreasing at alarming rates (Houlahan et al 2000;Stuart et al 2008).…”
mentioning
confidence: 98%
“…In the Americas and other parts of the world, corn cultivation is mainly based on genetically modified crops with a resistance against glyphosate, thus enabling repeated applications of glyphosate-based herbicides during cultivation (Duke and Powles 2008). Conversely, in most European countries, genetically modified crop cultivation is only marginal because most of such crops, with some exceptions such as Spain where nearly one third of corn cultivation is based on genetically modified plants (www.isaaa.org/), are still undergoing approval (Böll et al 2013). Since the beginning of this millennium, cycloxydim-resistant corn hybrids (which are not genetically modified) have gained growing importance (Vancetovic et al 2009) enabling repeated applications of the cycloxydim-based pesticide Focus Ultra (FO-UL), which is also used by foliar spraying against perennial grasses in conventional rape, sugar beet, potato, green bean, and field bean cultivations (EFSA 2010).…”
mentioning
confidence: 99%
“…Cooke 1981, Gillilland et al 2001, Eaton et al 2004, Piha et al 2006, Gurushankara et al 2007, Mann et al 2009, Böll et al 2013. The low prevalence of malformations found in this study could be explained to some extent by the fact that most baselines of prevalence of malformations are based on surveys that were carried out in industrialized countries in the Northern Hemisphere with longer histories of environmental pollution, while this study was performed in a developing country.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, wild bees (Schindler et al 2013, this issue) and amphibians (Böll et al 2013, this issue) were identified as sensitive species and thus important indicators in agricultural landscapes (Lang 2007). The experts identified particularly with regard to the availability and appropriateness of PMEM methodologies for non-target organisms substantial gaps.…”
Section: Vdi Guidelines For Pmemmentioning
confidence: 99%